Comparison of Hansen Solubility Parameter of Asphaltenes Extracted from Bitumen Produced in Different Geographical Regions - Sato, Takashi; Araki, Sadao; Morimoto, Masato; Tanaka, Ryuzo; Yamamoto, Hideki (Energy & fuels, 2014)
The Hansen solubility parameters (HSPs) of asphaltenes extracted from oil sand bitumen samples produced at Athabasca in Canada and also from a vacuum residue fraction (VR) produced in the Middle East were determined by the Hansen solubility sphere method. For calculation of HSPs, the solubilities of asphaltenes were determined using a dynamic light scattering (DLS) method by dissolving or dispersing the asphaltenes in various solvents and measuring the particle size distributions thereof. The particle diameters of asphaltenes in good solvents were lower than its detection limit (<1 nm). It was demonstrated in the present study that asphaltenes differing in elemental composition had different HSP values corresponding to dispersion, dipole interaction, and hydrogen-bonding forces (δd, δp, and δh, respectively). Experimental results suggested that the differences in HSP values of the asphaltenes were influenced by the H/C ratio, oxygen content, and average asphaltene molecular weight.